Síntese e Caracterização do Poli(PCL-TMC)uretana para utilização como Biomaterial - Gomes, Rodrigo Cesar (Universidade Federal de São Carlos, 2017)
Among the polymers widely investigated as materials for tissue engineering, polyurethane has its place of prominence, mainly due to the high flexibility and tenacity. The need for devices with certain mechanical properties combined with the ability to be biodegradable and bioreabsorbable motivates the scientific community to increasingly seek the creation of new materials in order to minimize the discomforts and increase the quality of life of the population. The present work aimed to synthesize a new copolymer produced from PCL and TMC with creation of urethane groups in the polymer chain. This synthesis combined the mechanical properties present in Polyurethane and PCL, with the increase of the modulus of elasticity conferred by the TMC, and allowed the increase of the degradation rate of the polyurethane due to the TMC. Prepolymer synthesis occurred in the bulk polymerization between PCL diol and TMC at 50/50 mass ratio using SnOct2 as catalyst. This synthesis was confirmed by FTIR and 1H NMR. The GPC analysis of three samples of the prepolymer showed Mn approximately 6000 g.mol-1 and Mw 12000 g.mol-1 with the IP close to 2. The poly (PCL-TMC) urethane formation occurred via solution polymerization between the prepolymer and HDI using solvent 1,2-dichloroethane and the molar ratio of 1: 2 (prepolymer / HDI). This synthesis was confirmed by FTIR and 1H NMR. Thermal characterization was performed using the DSC and TG techniques. There were no melt and crystallization temperatures in the DSC curve, indicating that the copolymer formed is probably amorphous, and the Tg found was -40 ° C. The TG indicated Tonset and Td, respectively 285 ° C and 301 ° C. Porous were made into the copolymer through solution freeze-drying and SEM test was performed on the porous material, and a mean pore diameter of approximately 38 μm was found, indicating the possibility of cell growth. Therefore, a new copolymer with potential application in biomaterials was created.
Synthesis and Characterization of Poly(PCL-TMC)urethane for use as Biomaterial
Keywords: Poliuretana; Policaprolactona; Trimetileno Carbonato; Biomaterial; Polyurethane; Polycaprolactone; Trimethylene Carbonate; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::BIOMATERIAIS E MATERIAIS BIOCOMPATIVEIS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES